Effect of nitrogen and phosphorus on the growth and yield performance of soybean (Research in Agriculture Livestock and Fisheries, 2015)
The experiment was conducted at the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh to study the effects of nitrogen and phosphorus on the performance of soybean. Three levels of nitrogen (0, 25 and 40 kg N ha-1) and four levels of phosphorus (0, 18, 36 and 54 kg P ha-1) were considered as treatment for the experiment. Soybean responded remarkably to the added nitrogenous and phosphatic fertilizers as the crop characters were significantly influenced by different levels of nitrogen and phosphorus. Significant effect on number of branches and seeds plant-1, plant height, number of filled pods plant-1, weight of seeds plant-1, dry weight of plant, stover weight plant-1, 1000-seed weight, seed and stover yield were obtained from the combined application of 25 kg N with 54 kg P ha-1.Res. Agric., Livest. Fish.2(1): 35-42, April 2015